Efficacy and safety of the combination of anlotinib and envafolimab in the treatment of unresectable or metastatic liposarcoma: findings from a single-center retrospective study - Liu, Hongliang; Hao, Qisheng; Wang, Xi; Cheng, Mengxing; Qiu, Fabo; Zhou, Bin (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the efficacy and safety of anlotinib combined with envafolimab in the treatment of unresectable or metastatic liposarcoma.MethodsThis single-center, retrospective study enrolled 15 patients with unresectable or metastatic liposarcoma, who were treated at the Retroperitoneal Tumor Surgery Research Center of Qingdao University Affiliated Hospital between April 2022 and November 2023. The treatment regimen consisted of anlotinib combined with envafolimab. Treatment efficacy was evaluated using the Response Evaluation Criteria in Solid Tumors version 1.1. Treatment-related adverse events (TRAEs) were assessed using Common Terminology Criteria for Adverse Events version 5.0.ResultsA total of 15 patients with unresectable or metastatic liposarcoma were included; among them, seven were male (46.7%) and eight were female (53.3%), with a median age of 55 years. The pathological subtype distribution was as follows: three (20.0%) patients with well-differentiated liposarcoma, 11 (73.3%) patients with dedifferentiated liposarcoma, and one (6.7%) patient with myxoid liposarcoma. At 12 weeks post-diagnosis, none of the patients achieved a complete response. The objective response rate was 6.7%, with one patient (6.7%) achieving a partial response. Disease stability was observed in 10 (66.6%) patients, which corresponded to a disease control rate of 73.3%. Disease progression occurred in four (26.7%) patients. The median follow-up time was 16.9 months and the median progression-free survival time was 14.2 months. Seven patients experienced TRAEs, of whom three (42.2%) had grade 3–4 TRAEs. The most common TRAEs were liver function abnormalities, hypertension, and fatigue.ConclusionAnlotinib combined with envafolimab demonstrates promising efficacy and manageable safety in treating unresectable or metastatic liposarcoma.